Mitigação dos inibidores gerados no pré-tratamento da biomassa vegetal: impacto técnico-econômico-ambiental de diferentes rotas de processo na biorrefinaria - Pinto, Ariane Silveira Sbrice (2021)
The presence of inhibitors is still an economic bottleneck that needs to be resolved in order to make 1G2G ethanol biorefineries feasible, requiring the development of technologies capable of improving their competitiveness in the biofuels marketplace. Soluble and insoluble lignin can impair the enzymatic hydrolysis process by inhibition, deactivation, and unproductive adsorption of enzymes. Washing the pretreated biomass or using lignin-blocking additives during saccharification could mitigate these negative effects in future biorefineries. Here, an investigation was performed of the combined mitigation processes, in terms of their technical and economic feasibility in a 1G2G sugarcane biorefinery. Evaluation was made of the impacts of biomass washing and soybean protein addition, separately or in combination, on glucose yields for hydrolysis in the presence of high (liquor) and low (buffer) concentrations of soluble inhibitors/deactivators. Combining washing and soybean protein addition provided the highest glucose yields, with an increase of up to 50%. The effect of the mitigation processes could be explained by a combination of catalytic mechanisms acting on both soluble and insoluble lignin. In an industrial context, biomass washing (90 ºC, 15% (w/w) solids, 3 steps) followed by soybean protein addition (12% (w/v) solids) provided a cost-competitive methodology for bioethanol production, with an estimated net present value of US$ 9.16x107, optimizing hydrolysis process in the 1G2G sugarcane biorefinery. Moreover, integrating both biomass washing and soybean protein addition units was a potential strategy for achieving a profitable and an eco-friendly biorefinery. The life cycle analysis of ethanol production showed that the categories of climate change and photochemical oxidation potentials were reduced if the washing process unit was considered in 1G2G biorefinery plant, with the most sustainable biorefinery achieved if only the soybean protein addition was included.